Tuning nanostructure and mechanical property of Fe–Co–Ni–Cr–Mn high-entropy alloy thin films by substrate temperature. (August 2021) - Hu, M.; Cao, Q.P.; Wang, X.D.; Zhang, D.X.; Jiang, J.-Z.
Abstract: Improving the mechanical property of high-entropy alloys (HEAs) with face-centered cubic (fcc) structure is critical for their potential applications. In this study, the effects of substrate temperature, T sub, on nanometer-sized structure and mechanical property of fcc-structured Fe–Co–Ni–Cr–Mn HEA thin films prepared by magnetron sputtering were systematically investigated. All films grow in a nanocolumnar manner and display a single fcc-structured solid solution phase with (111) preferential orientation in addition to the reduced amorphous phase fraction and increased average grain size with increasing T sub . The top-surface cauliflower-like hierarchical microstructure with some voided boundaries for 293 K-film gradually disappears with increasing T sub up to 573 K. For higher T sub (673 K–773 K), the obvious grain growth occurs with significantly increased column size and roughness. The variations in normal hardness, H, and Young's modulus, E s, obtained from nanoindentation tests on the surface of Fe–Co–Ni–Cr–Mn HEA thin films experienced a process of first increasing and then decreasing with T sub, with a maximum at T sub  = 573 K. The former increase is due to enhanced interfacial adhesion and the later decrease is ascribed to the weakened grain boundary strengthening caused by grain growth. The 573 K-film with a nanocomposite structure including hybrid nanocrystalline and amorphous phase exhibits the highest H (∼10.0 GPa) and E s (∼185.5 GPa) and is the strongest in terms of hardness among reported Fe–Co–Ni–Cr–Mn HEAs without post-treatment. In-situ micro-tensile tests alone the surface of Fe–Co–Ni–Cr–Mn HEA thin films uncovered the higher lateral yield strength (∼1.1 GPa), fracture strength (∼1.4 GPa), and Young's modulus (∼64.3 GPa) for 573 K-film than those of 293 K- and 773 K-films as well, consistent with nanoindentation results. Anisotropic mechanical responses normal to and along the surface were clearly found in Fe–Co–Ni–Cr–Mn HEA thin films, which are caused by the nanocolumnar morphology and the weakened columnar boundaries adhesion compared to the column itself. Graphical abstract: Image 1